Deregulation of tumor suppressive ASXL1−PTEN/AKT axis in myeloid malignancies. (1st April 2020) - Cao, Lei; Xia, Xianyou; Kong, Yu; Jia, Fengqin; Yuan, Bo; Li, Rui; Li, Qian; Wang, Yuxin; Cui, Mingrui; Dai, Zhongye; Zheng, Huimin; Christensen, Jesper; et al.
Abstract: Mutations of epigenetic regulators are pervasive in human tumors. ASXL1 is frequently mutated in myeloid malignancies. We previously found that ASXL1 forms together with BAP1 a complex that can deubiquitinylate mono-ubiquitinylated lysine 119 on histone H2A (H2AK119ub1), a Polycomb repressive mark. However, a complete mechanistic understanding of ASXL1 in transcriptional regulation and tumor suppression remains to be defined. Here, we find that depletion of Asxl1 confers murine 32D cells to IL3-independent growth at least partly due to sustained activation of PI3K/AKT signaling. Consistently, Asxl1 is critical for the transcriptional activation of Pten, a key negative regulator of AKT activity. Then we confirm that Asxl1 is specifically enriched and required for H2AK119 deubiquitylation at the Pten promoter. Interestingly, ASXL1 and PTEN expression levels are positively correlated in human blood cells and ASXL1 mutations are associated with lower expression levels of PTEN in human myeloid malignancies. Furthermore, malignant cells with ASXL1 downregulation or mutations exhibit higher sensitivity to the AKT inhibitor MK2206. Collectively, this study has linked the PTEN/AKT signaling axis to deregulated epigenetic changes in myeloid malignancies. It also provides a rationale for mechanism-based therapy for patients with ASXL1 mutations.